The level of household satisfaction with community-based health insurance and associated factors in Southern Ethiopia - Zepre, Kebebush (Frontiers in Public Health, 2023)
Background Community-based health insurance (CBHI) is a program intended to prevent financial hardship brought on by the cost of medical care. All of Ethiopia’s regions are implementing it; however, it has not yet been researched how the program is being received by the local population. This study’s objective is to determine how satisfied Southern Ethiopian households are with community-based health insurance programs and connected variables. Methods A community-based cross-sectional study was conducted from April to May 2021. Information was gathered from 528 households (HHs) selected at random in the Gurage Zone of Southern Ethiopia using a questionnaire. Bivariate and multivariate logistic regression, as well as descriptive statistics, were applied. p values less than 0.05 was used as a cutoff point for identifying the self-determining factors. Results The adjusted odds ratio (AOR) for HHs with the poorest wealth status was 2.40 (95% confidence interval:1.14–4.90); for HHs with a good knowledge of the CBHI, it was 1.81 (95% CI: 1.87–3.40); and for households with illness in the past 3 months, it was 5.22 (95% CI: 2.91–9.34). Recurrent visits to the facility (AOR:5.04, 95% CI:1.18-23.44), a Model household in rural health extension program (AOR:3.21, 95% CI:1.76-5.85), being enrolled in the scheme for three years or less (AOR:0.55, 95% CI: 0.30-0.95), and having faith in the leadership of the governing board (AOR:10.53, 95% CI:4.690-23.54) and the availability of the prescribed medication (AOR:14.64, 95% CI:5.37-39.84) were the significant influencing factors. Conclusion This study revealed several variables that affected HHs’ satisfaction with CBHI. We strongly advise all responsible parties to focus on increasing HH knowledge of the CBHI scheme, supporting HHs to serve as role models for rural health extension packages, and completing the CBHI pledged package to improve HHs’ satisfaction with the CBHI scheme, which may then play a role in the sustainability of CBHI.